Diseño de un catálogo on-line para la promoción y venta de productos elaborados por los artesanos del cantón playas - García Arnao, Isabel (2010)
Design of a catalogue online (www.hechoamano.com.ec) for the promotion and sale of products elaborated by the craftsmen of Playas Canton. This is a Web site in which one will show to a gallery of artisan exhibition with the works made by the craftsmen of Playas, impelling therefore the artisan manual labor of this part of the Ecuadorian coast, and obtaining the technological means inclusion that promotes these products. One appears in addition: • A brief description and photographies to the crafts. • A great variety of imitation jewellery done of tagua, nacre shell, shell to per it, seed of watermelon, crust of the Coco, leather, snails, diamonds of Brazil, stones of cat eye, to per it of river, chaquira, etc. • Crafts done in raft wood, as they are those of the naval strategy. • Crafts of Muyuyo and fabric of the Coco, etc. For the launching of this project it will be required approximately of an amount of initial investment of $9,600. In period of 6 months investor will obtain his first income significant, his gains will grow vertiginously, since our site will be the point of attraction for the companies that buy and sell artisan products of the Playas Canton, which wished to publicitar itself and to comprise of the Web site.